Brine rejection and hydrate formation upon freezing of NaCl aqueous solutions. Issue 14 (30th March 2020) - Tsironi, Ifigeneia; Schlesinger, Daniel; Späh, Alexander; Eriksson, Lars; Segad, Mo; Perakis, Fivos
Abstract : Studying the freezing of saltwater on a molecular level is of fundamental importance for improving freeze desalination techniques. Abstract : Studying the freezing of saltwater on a molecular level is of fundamental importance for improving freeze desalination techniques. In this study, we investigate the freezing process of NaCl solutions using a combination of X-ray diffraction and molecular dynamics simulations (MD) for different salt-water concentrations, ranging from seawater conditions to saturation. A linear superposition model reproduces well the brine rejection due to hexagonal ice Ih formation and allows us to quantify the fraction of ice and brine. Furthermore, upon cooling at T = 233 K, we observe the formation of NaCl·2H2 O hydrates (hydrohalites), which coexist with ice Ih. MD simulations are utilized to model the formation of NaCl crystal hydrates. From the simulations, we estimate that the salinity of the newly produced ice is 0.5% mass percent (m/m) due to ion inclusions, which is within the salinity limits of fresh water. In addition, we show the effect of ions on the local ice structure using the tetrahedrality parameter and follow the crystallite formation using the ion coordination parameter and cluster analysis.